Memória, cultura e patrimônio : possibilidades para o turismo cultural em Nova Petrópolis - Santos, Rodrigo José dos (My University, 2022)
This study aims to contribute with possibilities of cultural tourism through a rural community's history, located in Linha Imperial, Nova Petrópolis. Its intention is to benefit from elderly residents' memories in order to comprehend this community's building process and its developments. The research consists of the historical formation of Linha Imperial and the recognition of various memorable locations that are part of this history. In order to do so, the study relies on the theoreticalmethodological support of oral history, based on Portelli (2016). In addition to this method, information was sought in private and public archives, on official and private documents, photos, newspapers and testimonies already provided to other studies. The research is exploratory, of a qualitative nature, considering that the interviewed subjects are local residents. The data collection technique is going to be based on narrative interviews. The theoretical approach used is based on the work of Joel Candau (2014), Maurice Halbwachs (1990), Pierre Nora (1993), Denys Cuche (2002), Gessy Deppe (1988). The study about this community is seen to be able to contribute to the development of tourism in the city of Nova Petrópolis. The identification of cultural values present in this community can be used as a potential asset for cultural tourism. [resumo fornecido pelo autor]
O presente estudo teve como objetivo contribuir, por meio da história de uma comunidade rural, com a possibilidade de turismo cultural, a qual se localiza na Linha Imperial, em Nova Petrópolis, RS. Tem como intenção utilizar memórias de moradores mais velhos para compreender o processo de construção da comunidade e de seus desdobramentos. A pesquisa envolve a formação histórica da Linha Imperial, e o reconhecimento dos diversos lugares de memória, que fizeram parte dessa história. Para tal, o estudo conta com o suporte teórico-metodológico da história oral, baseado em Portelli (2016). Além desse método, buscou-se informações em acervos particulares e públicos, em documentos oficiais e privados, fotos, jornais e depoimentos já realizados em outras pesquisas. A pesquisa é exploratória, de natureza qualitativa, sendo que os sujeitos entrevistados são moradores da comunidade. A técnica de coleta de dados baseou-se na entrevista narrativa. O referencial teórico utilizado sustenta-se nas obras de Joel Candau (2014), Maurice Halbwachs (1990), Pierre Nora (1993), Denys Cuche (2002), Gessy Deppe (1988). Constata-se que o estudo dessa comunidade pode contribuir para o desenvolvimento do turismo no município de Nova Petrópolis, RS. A identificação dos valores culturais presentes na comunidade podem ser utilizados como potencial de turismo cultural.[resumo fornecido pelo autor]
Keywords: Turismo Cultural; Turismo - Nova Petrópolis (RS); Patrimônio Cultural; Comunidades - Nova Petrópolis (RS) - História; Heritage tourism; Tourism - Nova Petrópolis (Brazil); Cultural property; Community - Nova Petrópolis (Brazil) - History